Gerakan Masyarakat Sehat Jawa Timur di Era Pandemi Covid-19 dalam Perspektif Islam - Arini Indah Nihayaty (Moderasi : Journal of Islamic Studies, 2021)
The Healthy Community Movement (Germas) is part of an organized action that shapes behavior change in society in an effort to improve healthy living behavior. This movement is a movement launched by the president in 2017. During the COVID-19 pandemic, of course, the Germas program is very important in its implementation in society. In East Java, Germas is a very important movement in tackling cases of maternal and child mortality, stunting under five, leprosy, HIV, malaria and so on. East Java, which consists of 38 districts/cities, has several health problems. Cases of maternal and child mortality, stunting are high in three districts/cities in East Java. Therefore, this study has the aim to find out how the role of the healthy community movement during the COVID-19 pandemic in East Java and what obstacles are in the implementation of Germas in East Java. Obstacles in implementing Community Germas in East Java after the post-covid-19 pandemic. This study also looks at the implementation of Germas policies from an Islamic perspective. Therefore, the concept of Maqasid Syariah is also used in the study carried out. The study used a qualitative description, using observation or direct observation techniques. It uses phenomenology approach. The results of this study are the Community Movement (Germas) is part of an organized action that shapes behavior change in society in an effort to improve healthy living behavior and social solidarity which is part of Indonesian culture.